Re-expansion pulmonary edema after pleurocan catheterization: a case report - Mungan, İbrahim and Cankar Dal, Hayriye and Tatlısuluoğlu Ademoğlu, Derya and Tezcan, Büşra and Turan, Sema (The European Research Journal, 2018)
Re-expansion pulmonary edema (RPE) is a rare but potentially hazardous complication following evacuation of the pleural region. Symptomatic RPE occurs in less than 1% of patients after pleural drainage. Early diagnosis and treatment determines the progression of the disease and it is life-saving. The present case describes a 68-year-old man who developed RPE with the ipsilateral collapsed lung 6 hours after pleural drainage of a non-malignant effusion. He was intubated and 6 hours after aggressive treatment with mechanical ventilation support oxygenation was improved and the patient’s blood gas analysis recovered. Over the course of his 12-day hospitalization, he was extubated and oxygen support was slowly weaned down. Mortality rate of RPE in severe cases is approximately 20%, therefore preventive interventions gain importance. In spite of the rare incidence of RPE, being aware of this potential condition can allow for early and proper management.